Profil Berpikir Kreatif Siswa dalam Menyelesaikan Masalah Matematika Ditinjau dari Jenis Kelamin - Kharisma Isrozia Kusumawardhany; Mega Teguh Budiarto; Raden Sulaiman (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
The purpose of this research is to describe the profile of students' creative thinking in solving math problems in terms of gender. This type of research is a qualitative descriptive research. The subjects in this study were one male student and one female student. The two subjects had high and equal mathematical abilities. The research results obtained in this study were (1) The creative thinking profile of male students in solving math problems, namely at the (read and explore) stage of understanding the problem, the male subject found important elements in the problem including elements that were known and asked . After knowing what was asked in the question, the subject also knew and explained verbally every element of the information that was known and what was asked had a relationship. At the (select a strategy) stage of choosing a solution strategy, the male subject knows the various ideas used in solving TPM and can explain well the reasons for using these ideas so that this fulfills the flexibility indicator. At the (solve the problem) stage of carrying out problem solving, the male subject put forward various strategies used in solving the problem, namely by combining the rules of subtraction with multiplication of integers and using a number line. After knowing the ideas and strategies used, the subject implements these ideas and strategies in solving TPM problems so that this shows that the subject meets the indicators of fluency and novelty. At the (review and extend) stage of checking the answers again, the male subject verbally said that the solution to the problem was correct by checking the answers. The strategy used in checking answers with the rules of integer arithmetic operations is to see the results of changes in the temperature of each city and to make a number line so that in this case it meets the indicators of flexibility (flexibility) and fluency (fluency).